Overexpression of OsMYB305 in Rice Enhances the Nitrogen Uptake Under Low-Nitrogen Condition - Wang, Dujun; Xu, Tangqian; Yin, Zikui; Wu, Wenjuan; Geng, Haoting; Li, Long; Yang, Meng; Cai, Hongmei; Lian, Xingming (Frontiers in Plant Science, 2020)
Excessive nitrogen fertilizer application causes severe environmental degradation and drives up agricultural production costs. Thus, improving crop nitrogen use efficiency (NUE) essential for the development of sustainable agriculture. Here, we characterized the roles of the MYB transcription factor OsMYB305 in nitrogen uptake and assimilation in rice. OsMYB305 encoded a transcriptional activator and was induced by N deficiency in rice root. Under low-N condition, OsMYB305 overexpression significantly increased the tiller number, shoot dry weight, and total N concentration. In the roots of OsMYB305-OE rice lines, the expression level of OsNRT2.1, OsNRT2.2, OsNAR2.1, and OsNiR2 were upregulated and 15NO3- influx was significantly increased. In contrast, lignocellulose biosynthesis-related genes were repressed so that cellulose content decreased, and soluble sugar concentration increased. Certain intermediates in the glycolytic pathway and the tricarboxylic acid cycle were significantly altered and NADH-GOGAT, Pyr-K, and G6PDH were markedly upregulated in the roots of OsMYB305-OE rice lines grown under low-N condition. Our results revealed that OsMYB305 overexpression suppressed cellulose biosynthesis, thereby freeing up carbohydrate for nitrate uptake and assimilation and enhancing rice growth under low-nitrogen conditions. OsMYB305 is a potential molecular target for increasing NUE in rice.